1995
DOI: 10.1002/rcm.1290090906
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid composition and wavelength effects in matrix‐assisted laser desorption/ionization

Abstract: Ion yields were investigated in matrix-assisted laser desorption/ionization (MALDI) as a function of amino acid composition using a variable wavelength ion source. In the case of nitrogen laser excitation (337 nm), [M + H]+ ions were abundant for short peptides containing basic or polar amino acid residues. The lack of basic residues led to diminishing ion formation at 337 nm. Increasing the chain length led to enhanced ionization even for peptides with non-polar side chains. In contrast to the liquid phase ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
1
46
1
Order By: Relevance
“…Detailed description of the system can be found elsewhere. 7 Briefly, the MALDI-generated ions were accelerated to 10-30 kV and ejected into the field-free region of a time-of-flight (TOF) mass spectrometer. The ions were detected by a dual-microchannel plate (Galileo Electro-Optics Co., Sturbridge, MA) that was biased to 1900 V. The ion currents were amplified (×10) and recorded by a 200 MHz transient recorder (TR8828D, LeCroy, Albuquerque, NM).…”
Section: Methodsmentioning
confidence: 99%
“…Detailed description of the system can be found elsewhere. 7 Briefly, the MALDI-generated ions were accelerated to 10-30 kV and ejected into the field-free region of a time-of-flight (TOF) mass spectrometer. The ions were detected by a dual-microchannel plate (Galileo Electro-Optics Co., Sturbridge, MA) that was biased to 1900 V. The ion currents were amplified (×10) and recorded by a 200 MHz transient recorder (TR8828D, LeCroy, Albuquerque, NM).…”
Section: Methodsmentioning
confidence: 99%
“…Strong evidence for proton transfer reactions between protonated matrix and analyte was recently reported using mixtures of conventional matrices and various amino acids varying in gas phase basicity [6]. In peptide analysis it was shown that the type of amino acid incorporated in the peptide backbone affects the abundance of the corresponding ions generated [14]. In particular, MALDI spectra of peptides derived from proteolytic digestion of proteins with trypsin indicated that the proton affinity of Cterminus amino acids governs the MALDI response of the resulting peptide ions and lysine containing peptides generated by tryptic digestion of proteins produce ions detected in lesser abundance than those incorporating arginine [15].…”
mentioning
confidence: 97%
“…This allowed for tests of various hypotheses that were put forward in recent literature e.g., about influence of peptide hydrophobicity on signal intensity [13]. To elucidate how the amino acids are distributed at every position in the peptide sequence, we calculated the relative entropy [14,15] of each amino acid at every position and the potential of the peptides to form secondary structures as described by Williams et al [16] and Wilmot and Thornton [17].…”
mentioning
confidence: 99%